A study on the extension of correlation functions obtained from molecular dynamics simulations by the Ornstein–Zernike theory for modeled molten salts - Tatsuhiko Miyata; Yu Funahara; Seiya Omori; Taro Shinjo (AIP Advances, 2023)
We extend the correlation functions obtained by molecular dynamics (MD) simulation for a molten salt modeled as a superposition of the Lennard-Jones (LJ) and Coulomb potentials using the hybrid closure method, which employs the Ornstein–Zernike (OZ) theory coupled with a closure relation. An appropriate distance for switching the short-range MD part and the long-range OZ part is determined by monitoring the isothermal compressibility, excess internal energy, and pressure. The Kobryn–Gusarov–Kovalenko (KGK) closure relation is mainly employed for the hybrid closure method (MD–KGK hybrid closure). The hybrid closure with either the hypernetted chain (HNC) or Kovalenko–Hirata (KH) closure was also tested to confirm that the performance was almost equivalent to one another among the MD–HNC, MD–KH, and MD–KGK methods. The bridge function for the model molten salt is extracted using the MD–KGK hybrid closure method. At a high-density state, the bridge function shows a steep increase in the repulsive core region, as is often observed for simple fluids, whereas when the density is relatively low, the bridge function for the cation–anion pair shows a downward-sloping behavior. Furthermore, the accuracies of excess internal energy, pressure, and isothermal compressibility were also examined for the HNC, KH, and KGK approximations. For molten salt systems, these approximations exhibited a similar behavior to those for monatomic LJ fluids, especially in the high-density state. The analysis of the integrand for excess internal energy and pressure is also discussed.